1982
DOI: 10.1007/bf00388999
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature on the functional response of the dragonfly Celithemis fasciata (Odonata: Libellulidae)

Abstract: 1) Functional response curves were constructed for Celithemis fasciata larvae feeding on 6 different densities of midge larvae at 10, 15, 20, and 25°C. Values for attack rate and handling time were estimated with Rogers's random predator equation. 2) Polynomial regression revealed that the functional response curves were linear although a tendency toward decreasing consumption rates at higher densities was shown. 3) The mean number of prey eaten increased with temperature; however, temperature did not alter th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
5
32
0
Order By: Relevance
“…However, the Type II functional response characteristic of dragonfly nymphs (Gresens et al 1982, Cothran andThorp 1984) would not dampen oscillations in prey abundance. Moreover, we found no evidence of switching when Celithemis fasciata was given a choice between the midge Chironomus tentans and the cladoceran Daphnia magna (Cothran and Thorp 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Type II functional response characteristic of dragonfly nymphs (Gresens et al 1982, Cothran andThorp 1984) would not dampen oscillations in prey abundance. Moreover, we found no evidence of switching when Celithemis fasciata was given a choice between the midge Chironomus tentans and the cladoceran Daphnia magna (Cothran and Thorp 1984).…”
Section: Discussionmentioning
confidence: 99%
“…From laboratory studies it is known that odonates exhibit a nonstabilizing, Type II functional response (sensu Holling 1959) to changes in prey density (e.g., Johnson 1973, Thompson 1975, Akre and Johnson 1979, Gresens et al 1982. The effects of dragonflies on prey density and species composition in the field have been examined in ponds (Benke 1976), large pens (Benke 1978), and small, submerged aquaria (Benke et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of varying temperature on the functional response of odonate larvae have been studied extensively in a number of species (Gresens et al 1982;Thompson 1978c). Higher temperatures result in an increase in the asymptotes of the type II functional response in Ischnura elegans.…”
Section: Ecology Trophic Interactionsmentioning
confidence: 99%
“…This was manifested in an increase in the attack coefficient and a decrease in handling time at higher temperatures (Thompson 1978c). The increased feeding rates at higher temperatures have also been linked to an increase in the rate of gut clearance at higher temperatures (Gresens et al 1982). Clearly an increase in feeding rate in a top predator in aquatic ecosystems (e.g.…”
Section: Ecology Trophic Interactionsmentioning
confidence: 99%
“…Data are means ± 1 SE ambient treatment in the presence of predators, the underlying mechanism can be explored by analyzing behavioral responses of tadpoles to increased predation risks. Previous studies showed that activity level and associated metabolic rate are higher at high temperatures (Gresens et al 1982;Jayakumar and Mathavan 1991). For example, Bailey (1988) found that notonectid swimming activity increased with temperature, and consistently an inverse relationship was found between temperature and gut clearance for Fig.…”
Section: Discussionmentioning
confidence: 69%